Kinetics and mechanism of N-chlorosaccharin oxidation of malic acid - Singh, Sanjay Kumar (2010)
Kinetic study of N-chlorosaccharin (NCSA) oxidation of malic acid (MA) in aqueous acetic acid medium in presence of perchloric acid has been investigated. The reactions exhibit first-order dependency in oxidant and HClO4 while order varies from one to zero in substrate. The reactions are acid catalyzed and retarded by the addition of saccharin, a byproduct of reaction. The rate of oxidation decreases with decrease in dielectric constant of the medium. The effect of temperature on the reaction has been investigated in the temperature range 313-333 K. The stochiometric studies revealed 1:1 mole ratio. Various thermodynamic parameters have been computed and a possible operative mechanism is proposed.